Modelamiento de un sistema solar fotovoltaico a nivel utility (2020)
The modeling of the photovoltaic system of the Julio Mario Santo Domingo building was developed with the functions and models of the Python pvlib library made by Sandia National Laboratories. This modeling was carried out first using the irradiance and temperature registered in Meteocontrol, which is the monitoring system of this plant, and later with the irradiance and temperatures obtained through a forecast also available in pvlib and it was compared with the contemporary production registered in Meteocontrol. Finally, these models were joined to a graphical interface using the tkinter library, also from Python, to allow modeling different systems with different sizes and characteristics, such as utility-level systems. All this resulted in the testing of the models and the finding that a modeling based on the forecast available in pvlib is not the optimal option to perform this task, despite the fact that this option is always available. The optimal option would then be to model from the information of the typical meteorological year (TMY) or of the APIs available on the internet.